Improving students' Spiritual Intelligence Through Compulsory Dormitory Program - Surawan Surawan; Rahmat Tawakkal Sobari (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2022)
Spiritual Intelligence is one of the three types of intelligence. It has a fundamental role, especially in Islamic education. As one of the Islamic higher education institutions, IAIN Palangka Raya has a unit named Ma'had Al-Jami'ah IAIN Palangka Raya. This technical implementation unit aims to be a support system in building and forming religious and insightful students. This study aims to determine what programs Ma'had Al-jami'ah IAIN Palangka Raya organize to train students’ spiritual intelligence. The method used is an observation method with the target of Islamic Religion Education 2021 generation Rolling 1st students. However, in the direction of the compulsory dormitory program aims to train the Spiritual Intelligence of all parties involved in Ma'had Al-Jami'ah IAIN Palangka Raya, both advisors, and students. The results show that the compulsory dormitory program can improve students' spiritual intelligence because it consists of attitude development activities, dhikr therapy, and good habits. Spiritual Intelligence merupakan salah satu dari ketiga jenis kecerdasan yang meliputi Intelectual Quotient (Kecerdasan Intelektual) dan Emotional Quotient (Kecerdasan Emosional). Ma’had Al-Jami’ah IAIN Palangka Raya merupakan lembaga pendidikan yang termasuk dalam Unit Pelaksana Teknis (UPT) yang ada di kampus IAIN Palangka Raya yang bertujuan untuk menjadi Support Syestem dalam pembentukan karakter mahasiswa yang agamis, religius dan berwawasan luas. Artikel ini dibuat bertujuan untuk mengetahui apa saja program yang diselenggarakan oleh pengurus UPT Ma’had Al-Jami’ah IAIN Palangka Raya dalam melatih Spiritual Intelligence Mahasantri Ma’had Al-Jami’ah IAIN Palangka Raya. Metode yang digunakan dalam penyusunan artikel ini adalah metode observasi dengan target mahasiswa PAI 2021 Rolling ke-1. Hasil penelitian menunjukkan bahwa program asrama wajib dapat meningkatkan spiritual intelligence mahasiswa, karena di dalamnya terdapat kegiatan pembinaan sikap, terapi dzikir dan pembiasaan yang baik.